PERKEMBANGAN INDUSTRI PENERBANGAN DAN PERTUMBUHAN EKONOMI DI INDONESIA - bayu dananjaya utama (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2021)
Competition in the air transportation service business is currently experiencing very rapid development. This study looks at the effect of economic growth, population density, the number of provincial land transportation in Indonesia on the number of passengers and the number of cargo. This study uses statistical data on air transportation released by the Central Statistics Agency (BPS). The regression method used is the Fixed Effect. The results of this study indicate that GDP per capita and government policies regarding upper and lower limit fares are indicated to have a significant positive effect on the number of passengers when not using the time trend. Furthermore, trucks are indicated to have a significant positive effect on cargo when they do not use the time trend. The policy to impose tariff limits can upset the market balance. When the application of the upper limit rate is below the equilibrium price, it can cause excess demand.